Analysis of lung tumor initiation and progression in transgenic mice for Cre-inducible overexpression of Cul4A gene - Wang, Yang (Thorac Cancer, 2015)
BACKGROUND: Lung cancer is the leading cause of morbidity and death worldwide. Although the available lung cancer animal models have been informative and further propel our understanding of human lung cancer, they still do not fully recapitulate the complexities of human lung cancer. The pathogenesis of lung cancer remains highly elusive because of its aggressive biologic nature and considerable heterogeneity, compared to other cancers. The association of Cul4A amplification with aggressive tumor growth and poor prognosis has been suggested. Our previous study suggested that Cul4A is oncogenic in vitro, but its oncogenic role in vivo has not been studied. METHODS: Viral delivery approaches have been used extensively to model cancer in mouse models. In our experiments, we used Cre-recombinase induced overexpression of the Cul4A gene in transgenic mice to study the role of Cul4A on lung tumor initiation and progression and have developed a new model of lung tumor development in mice harboring a conditionally expressed allele of Cul4A. RESULTS: Here we show that the use of a recombinant adenovirus expressing Cre-recombinase (“AdenoCre”) to induce Cul4A overexpression in the lungs of mice allows controls of the timing and multiplicity of tumor initiation. Following our mouse models, we are able to study the potential role of Cul4A in the development and progression in pulmonary adenocarcinoma as well. CONCLUSION: Our findings indicate that Cul4A is oncogenic in vivo, and this mouse model is a tool in understanding the mechanisms of Cul4A in human cancers and for testing experimental therapies targeting Cul4A.